O-GlcNAcylation, contractile protein modifications and calcium affinity in skeletal muscle - Cieniewski-Bernard, Caroline; Lambert, Matthias; Dupont, Erwan; Montel, Valérie; Stevens, Laurence; Bastide, Bruno (Frontiers in Physiology, 2014)
Phosphorylation is recognized as being one of the major post-translational modification involved in the fine modulation of all if not all cellular processes including skeletal muscle contractile activity. However, phosphorylation presents a dynamic and highly regulated interplay with an atypical glycosylation on intracellular proteins, the O-GlcNAcylation. Akin to phosphorylation, O-GlcNAcylation is also involved in the physiopathology of several acquired diseases, such as muscle insulin resistance in diabetes or muscle atrophy. Recent data underline that the interplay between phosphorylation and O-GlcNAcylation acts as a modulator of skeletal muscle contractile activity. In particular, the O-GlcNAcylation level of the phosphoprotein MLC2 seems to be crucial in the modulation of the calcium activation properties, and should be responsible of changes in calcium properties observed in atrophy. Moreover, since several key structural proteins are O-GlcNAc-modified, and because of the localization of the enzymes involved in the O-GlcNAcylation/de-O-GlcNAcylation process to the nodal Z disk, a role of O-GlcNAcylation in the modulation of the sarcomeric structure should be considered.